GROWTH AND YIELD OF MORINGA PLANTS (moringa oleifera Lam.) GIVEN SEVERAL DOSAGES OF PHOSPHATE FERTILIZER AND GROWN ON VARIOUS TYPES OF SOIL - I K., Kusnaedi; Trisnadewi, A. A. A. S.; Suarna, I W. (Jurnal Peternakan Tropika, 2019)
The research aimed to determine the growth and yield of moringa plants ( Moringa oleifera Lam.) which are given several dosage of phosphate fertilizer and grown on various types of soil. The study was conducted out for 3 months in the Greenhouse, Sading Village, Mengwi District, Badung Regency, Bali. The experimental design used was a completely randomized design (CRD) of a nested pattern. The first factor was the type of soil, consist of: mediterranean soil, latosol soil, and regosol soil and the second factor was the dosage of phosphate fertilizer (TSP), consist of: P 0 = control, P 50 = 50 kg / ha, and P 100 = 100 kg / ha. The variables observed were growth variables, yields and characteristics of plant growth. The results showed that the growth of Moringa oleifera Lam planted on various types of soil showed significantly different results, but not significantly different to root length. Additional of several dosage of phosphate fertilizer showed no significant difference in all growth variables. Yield variables show significantly different results, but not significantly different in the administration of several dosage of phosphate fertilizer. The growth characteristics showed different which were not significant, but significantly different from the variable ratio of leaf dry weight to root dry weight, ratio of total forage dry weight to root dry weight and leaf area. Additional of several dosage of phosphate fertilizer showed not significant different. It can be concluded that the planting of Moringa oleifera gave better growth and yields on regosol and latosol soil than in Mediterranean soil. The dosage of phosphate fertilizer 50 kg / ha and 100 kg / ha haved no effect on the growth and yield of Moringa oleifera .   Keywords: growth and yield, Moringa oleifera, type of soil, dosage of phospahte fertilizer